2019
DOI: 10.11152/mu-1679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of regional myocardial perfusion in methamphetamine abusers using real-time myocardial contrast echocardiography

Abstract: Aims: To evaluate the feasibility of assessing regional myocardial perfusion using real-time myocardial contrast echocardiography (MCE) at rest for detecting coronary microcirculation abnormalities in methamphetamine abusers.Material and methods: Twenty-two male methamphetamine abusers (11 without chest pain, 11 with chest pain), free of ascertained coronary artery disease, were enrolled in this study. A control group of 22 age-matched male healthy participants was studied for comparison. Standard 2D, flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…If the time of myocardial contrast imaging is delayed, it indicates abnormal microcirculation perfusion [23] . The decrease of myocardial perfusion may be closely related to the occurrence and development of myocardial injury [24] . Abnormal microcirculation perfusion can not only early reflect chemotherapeutic myocardial microvascular disease, but also serve as an independent prognostic factor [25] .…”
Section: Discussionmentioning
confidence: 99%
“…If the time of myocardial contrast imaging is delayed, it indicates abnormal microcirculation perfusion [23] . The decrease of myocardial perfusion may be closely related to the occurrence and development of myocardial injury [24] . Abnormal microcirculation perfusion can not only early reflect chemotherapeutic myocardial microvascular disease, but also serve as an independent prognostic factor [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease is common in MA abusers. Early coronary microcirculation abnormalities and reduced myocardial perfusion can be detected by myocardial contrast echocardiography . In an Australian study of 894 MA‐associated deaths, autopsy showed a high prevalence of coronary artery disease (19%), LV‐dilatation (26.3%), LV‐hypertrophy (19%), myocardial scarring (19.8%) despite the young mean age of 37.9 years .…”
Section: Cardiac Complicationsmentioning
confidence: 99%
“…3D speckle tracing imaging markers are useful for early detection of ventricular dysfunction . Contrast echocardiography may be helpful in detecting early microvascular changes and myocardial ischaemia . Left heart catheterization should be performed to exclude coronary artery disease and, in the case of suspected myocarditis, to obtain myocardial biopsies.…”
Section: Cardiac Complicationsmentioning
confidence: 99%
“…Studies have shown that HCM patients with normal coronary angiography still have different degrees of myocardial ischemia, which is essentially coronary microvascular dysfunction [ 7 ]. Coronary microcirculation disorders and the effect of reperfusion therapy and clinical prognosis [ 8 , 9 ] can be accurately assessed by observing myocardial microcirculation perfusion [ 10 ] and assessing myocardial blood flow (MBF) with myocardial contrast echocardiography (MCE), which is of great importance to the clinical diagnosis and treatment of HCM.…”
Section: Introductionmentioning
confidence: 99%